Pengaruh Motivasi Kerja, Budaya Organisasi, dan Lingkungan Kerja Terhadap Kinerja Karyawan pada Perumda Air Minum Tirto Negoro Kabupaten Sragen - Muhammad Akbar Zulkifli; Sarsono; Istiqomah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The researchers at the Tirto Negoro Drinking Water Company set out to find out what makes workers there tick, which is located in the Sragen Regency. These factors include work motivation, organizational culture, and the work environment.This study is quantitative in nature and employs many methods of data analysis, including testing of classical assumptions, testing of hypotheses, testing of the coefficient of determination, and testing of statistical models with multiple linear regressions. In this study, there were a total of one hundred employees that participated. There were 54 regular employees at the Tirto Negoro Drinking Water Company, which is located in the Sragen Regency. This constituted the sample. In this investigation, the sampling approach employed was saturation sampling.This study's findings demonstrate that three factors significantly affect organizational performance: work environment, motivation, and organizational culture. A total of 58.7% of the components contribute to the coefficient of determination; the remaining 41.3% is explained by other variables not included in the research model.